Kritične uprizoritvene prakse od neoavantgarde in postavantgarde do političnega postdramskega gledališča 21. stoletja - Toporišič, Tomaž (Amfiteater (Ljubljana), 2025)
The essay examines four key cycles of revolutionary transformations in the relationship between mainstream and experimental theatre in Slovenia and the former Yugoslavia: the neo-avant-garde and neo-modernism of the 1970s, the political theatre of the 1980s, the post- and retro-avant-garde of the 1990s, and the post-postdramatic documentary theatre of the 21st century. The first three cycles reinterpret the utopian ideas of historical avant-gardes, adapting them to new political contexts, while the fourth cycle situates them within the framework of critical art in the post-socialist and neoliberal era of liquid modernity (Bauman). The discussion is grounded in Piotr Piotrowski’s concept of horizontal art history and the redefinition of the centre and the periphery, in which the periphery does not function merely as an extension of the core (Mishkova) but rather establishes its own autonomy and alternative models of collective identification. Through selected case studies, we explore how experimental practices have subverted dominant cultural paradigms and challenged the hegemony of late capitalism, following Boris Groys’s argument that artists themselves are the primary consumers of art. Furthermore, we demonstrate how artists from different generations and historical-political contexts develop aesthetically, socially and politically transgressive theatrical practices that investigate and challenge the boundaries of individual and cultural identity. These practices dismantle the idealistic vision of a harmonious public sphere while simultaneously fostering and deconstructing the illusion that art can truly contribute to the disarmament of libidinal forces (Mouffe) that fuel hostility and are ever-present in human societies – ultimately questioning the renunciation of death as an instrument of decision-making.
Keywords: East art map; Lado Kralj; liquid modernity; neoavantgarda; neo-avant-garde; Oliver Frljić; postavantgarda; post-avant-garde; tekoča moderna